Formalisasi Industri Pengolahan di Kabupaten Kebumen: Sebuah Tantangan - Dodi Satriawan (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2023)
The purpose of this study is to examine the challenges of manufacturing formalization in Kebumen Regency. This study uses secondary data from BPS, the 2016 Economic Census-Continued, as a data source. The data analysis method used in this study is descriptive analysis. The analysis was carried out through cross tabulation to obtain an overview of the characteristics and challenges of manufacturing formalization in Kebumen Regency. The results of the study indicate that the challenges of manufacturing formalization can be seen from the legal, social, economic and management dimensions. Some of these challenges include business legality, low level of education of entrepreneurs, low access to bank credit, lack of partnerships, lack of business development plans, and low computer and internet use.